Pathology-pain relationships in different osteoarthritis animal model phenotypes: it matters what you measure, when you measure, and how you got there. Issue 10 (October 2021) - Zaki, S.; Smith, M.M.; Little, C.B.
Summary: Objective: To determine whether osteoarthritis (OA) pain characteristics and mechanistic pathways in pre-clinical models are phenotype-specific. Design: Male 11-week-old C57BL6 mice had unilateral medial-meniscal-destabilization (DMM) or antigen-induced-arthritis (AIA), vs sham-surgery/immunised-controls (Sham/Im-CT). Pain behaviour (allodynia, mechanical- and thermal-hyperalgesia, hindlimb static weight-bearing, stride-length) and lumbar dorsal root ganglia (DRG) gene-expression were measured at baseline, day-3, week-1/-2/-4/-8/-16, and pain-behaviour:gene-expression:joint-pathology associations investigated. Results: DMM and AIA induced structural OA defined by progressively increasing cartilage erosion, subchondral bone sclerosis and osteophyte size and maturation. All pain-behaviours were modified, with model-specific differences in severity and temporal pattern. Tactile allodynia developed acutely in both models and persisted to week-16. During early-OA (wk4-8) there was; reduced right hindlimb weight-bearing in AIA; thermal-hyperalgesia and reduced stride-length in DMM. During chronic-OA (wk12-16); mechanical-hyperalgesia and reduced right hindlimb weight-bearing were observed in DMM only. There were no associations in either model between different pain-behaviour outcomes. A coordinated DRG-expression profile was observed in sham and Im-CT for all 11 genes tested, but not in AIA and DMM . At wk-16 despite equivalent joint pathology, changes in DRG-expression ( Calca, Trpa1, Trpv1, Trpv4 ) were observed only in DMM. In AIA mechanical-hyperalgesia was associated with Trpv1 ( r  = −0.79) and Il1b ( r  = 0.53). In DMM stride-length was associated with Calca, Tac1, Trpv1, Trpv2, Trpv4 and Adamts5 ( r  = 0.4–0.57). DRG gene-expression change was correlated with subchondral-bone sclerosis in DMM, and cartilage damage in AIA. Positive pain-behaviour:joint-pathology associations were only present in AIA - for synovitis, subchondral-bone resorption, chondrocyte-hypertrophy and cartilage damage. Conclusion: Pain and peripheral sensory neuronal responses are OA-phenotype-specific with distinct pathology:pain-outcome:molecular-mechanism relationships.